Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0188522
|View full text |Cite
|
Sign up to set email alerts
|

Can narrow-bandwidth light from UV-A to green alter secondary plant metabolism and increase Brassica plant defenses against aphids?

Abstract: Light of different wavelengths is essential for plant growth and development. Short-wavelength radiation such as UV can shift the composition of flavonoids, glucosinolates, and other plant metabolites responsible for enhanced defense against certain herbivorous insects. The intensity of light-induced, metabolite-based resistance is plant- and insect species-specific and depends on herbivore feeding guild and specialization. The increasing use of light-emitting diodes (LEDs) in horticultural plant production sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Nevertheless, blue light was not able to further increase flavonoid glycosides and hydroxycinnamic acids in Brassicaceae sprouts. However, in broccoli, kaempferol-3-feruloyl-sphoroside-7-glucoside and kaempferol-3-caffeoyl-sophoroside-7-glucoside were increased after blue light treatment alone, without any UV pre-treatment ( Rechner et al, 2017 ). Blue light was able to increase total phenolics of lettuce ( Johkan et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, blue light was not able to further increase flavonoid glycosides and hydroxycinnamic acids in Brassicaceae sprouts. However, in broccoli, kaempferol-3-feruloyl-sphoroside-7-glucoside and kaempferol-3-caffeoyl-sophoroside-7-glucoside were increased after blue light treatment alone, without any UV pre-treatment ( Rechner et al, 2017 ). Blue light was able to increase total phenolics of lettuce ( Johkan et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such effects have been attributed to blue/UV-A absorbing cryptochromes, which can play a role in shade avoidance (Keller et al, 2011). However, there are also studies that reported that UV-A radiation decreased plant height (D ader et al, 2014;Rechner et al, 2017). In this context, more evidence is needed to corroborate speculations about UV-A radiation playing a functional role in countering the shade-acclimated phenotype.…”
Section: Treatmentsmentioning
confidence: 99%
“…In contrast, traditional farming techniques increase sunlight and simultaneously UV radiation during plant growth and ripening to increase secondary plant metabolites that contribute to flavor and color, e.g., reduction of leaves in the vine during berry ripening [ 16 , 17 ]. Recent studies, however, have highlighted the regulatory properties of low, ecologically relevant UVB levels that trigger the accumulation of certain flavonoids, known for their high antioxidant activity, in Brassica species [ 11 , 18 , 19 , 20 , 21 ] and other species [ 14 , 22 ]. Flavonoid enrichment also affects plant quality and is important in meeting consumer preferences for fruits and vegetables, including growth and appearance, aroma/smell, flavor, color, and compounds that promote plant and human health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%